Low-temperature properties of nematic liquid crystal materials for display. Issue 11 (2nd September 2021) - Gao, Na; Jing, Shuai; Kong, Xiangming; Wu, Nan; Wu, Keming; Sun, Jingjing; Cai, Minglei; Zhao, Tongzhou; Yang, Changyong; Xing, Hongyu; Ye, Wenjiang
ABSTRACT: The orientation of Nematic liquid crystal (NLC) and order degree of LC molecules are easily affected by ambient temperature, so it is of great significance to explore the low-temperature properties of NLC materials to improve the low-temperature performance of LC devices. The dielectric and elastic constant of the NLC material 1M10500-000 under the high and low-temperature conditions were obtained by the dual-cell capacitance method, linear fitting method and numerical fitting, and were compared. The dynamic response of the NLC at different temperatures was tested, and the rotational viscosity was calculated. The experimental results show that the dielectric constant is still proportional to the order parameter at low temperature. The elastic constants k 11 and k 33 and the square of order parameter no longer conform to the proportional relationship at low temperature, and the lower the temperature, the greater the deviation of elastic constants from the proportional relationship. As the temperature decreases, the ratio of k 33 / k 11 changes from 2.62 to 2.71, and the rotational viscosity coefficient changes from 5.66 mPa.s to 177.64 mPa.s. Finally, the transient hysteresis phenomenon at low temperature was proposed and explained by the residual direct current voltage. Graphical abstract: uf0001